Role of organizational network analyses to advance workforce inclusion and belonging: a scoping literature review - Decker-Tonnesen, Patrick L.; Chesak, Sherry S.; Walker, Laura E.; Kohler, Katharina; Phelan, Sean; Gunnels, Marshall S.; Saliba, Kara L.; Bhagra, Anjali (Frontiers in Psychology, 2025)
Organizational Network Analyses (ONAs) are tools used to explore the strengths and challenges in the human relationships that occur within organizations. ONAs consist of matrices of informal and formal connections that help to identify potential patterns of inclusion and exclusion across organizational systems. Understanding the directions of workplace relationships is critical for advancing workforce inclusion and belonging. To better understand the efficacy of organizational networks for inclusion and belonging, this scoping literature review included fifteen studies that met inclusion criteria and were placed into five categories including: Studies With Gender-Related Outcomes; Studies With Race, Ethnicity, and Culture-Related Outcomes; Studies With Cross Gender-Related and Race, Ethnicity, and Culture-Related Outcomes; Studies With Academic Medical Setting-Related Outcomes; and Studies With Miscellaneous Outcomes. Results demonstrated ONAs are a useful tool for organizations to better understand barriers to inclusion and belonging, including for employee gender and race. Additionally, ONAs help provide information to organizations on network differences and connectivity within groups. The findings of this review warrant future research to further assess how ONAs interact with dimensions of difference and workplace inclusion and belonging.